HUBUNGAN TEHNIK PEMASANGAN DAN PERAWATAN KATETER DENGAN INSIDENSI INFEKSI SALURAN KEMIH DI RS PKU MUHAMMADIYAH YOGYAKARTA - La Ode Abd Rahman (PSIK 11 UMY, 2011)
Urinary tract infection is an infection that is caused by growth of abnormal bacteria in the bladder, with urine culture examination found that bacteria >105 cfu/ml. The development of bacteria in urine usually accompanied by symptomatic and asymptomatic, that is caused by various factors such as poor perineal hygiene, and non-sterile catheterization. Sterile catheter insertion technique and aseptic catheter care can reduce urinary tract infection. The purpose of this research was to know the